An ounce of prevention : marketing, sales, and advertising law for non-lawyers - Meyerowitz, Steven A., 1955- (Detroit : Visible Ink, 1994)
Advertising. Sales people. Legal restrictions on marketing. Customer relations. Especially for marketing executives.
Keywords: Marketing; Law; United States; Law and legislation; Advertising laws; Marketing -- Law and legislation -- United States; Advertising laws -- United States; Sales -- United States; Business law -- United States